2002
DOI: 10.1051/0004-6361:20021544
|View full text |Cite
|
Sign up to set email alerts
|

A spectro-astrometric study of southern pre-main sequence stars

Abstract: Abstract. We present spectro-astrometric observations for 28 southern pre-main sequence (PMS) stars and investigate their circumstellar environment down to AU scales. The structures detected in the "position spectra" include: (1) almost all the known binary companions in our sample (Sz 68, Sz 41, HO Lup, VW Cha, S CrA, AS 205), (2) companion candidates which have not been detected by infrared speckle techniques (T CrA, MWC 300), (3) monopolar and bipolar jets (AS 353A, CS Cha), (4) a combination of jets and a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
139
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(155 citation statements)
references
References 86 publications
14
139
2
Order By: Relevance
“…Reipurth et al (2002) report from their spectroscopy data, with the primary and secondary situated in the spectrograph entrance window, that the object is a spectroscopic binary candidate with a possible period of about 125 days. While the spectro-astrometric displacement found by Takami et al (2003) is small and might be caused by the binarity also recovered by us at ∼2 arcsec, Covino et al (1997), Melo (2003), Guenther et al (2007) and Joergens (2008) all found no evidence of a spectroscopic binarity.…”
Section: Sz 41supporting
confidence: 42%
“…Reipurth et al (2002) report from their spectroscopy data, with the primary and secondary situated in the spectrograph entrance window, that the object is a spectroscopic binary candidate with a possible period of about 125 days. While the spectro-astrometric displacement found by Takami et al (2003) is small and might be caused by the binarity also recovered by us at ∼2 arcsec, Covino et al (1997), Melo (2003), Guenther et al (2007) and Joergens (2008) all found no evidence of a spectroscopic binarity.…”
Section: Sz 41supporting
confidence: 42%
“…For these simulations, we assume a point-symmetric extended component (for which we use the 2-GAUSS geometry discussed in Sect. 4.2) and add a compact companion at a separation of 60 mas, corresponding to the minimum separation of the proposed wide-separation companion star (Takami et al 2003). Then, we compute the residuals between the model with and without companion star and measure the amplitude of the wavelength-differential visibility and CP modulation for the K-band spectral window.…”
Section: Binary: Asymmetric Two-component Gaussian Modelmentioning
confidence: 99%
“…by Takami et al (2003) line emission regions slightly off-set from the center of the continuum emission can in theory also be produced by unresolved, very close binary components. However, for our edge-on object a jet origin of the observed forbidden-line emission appears much more plausible.…”
Section: Wind and Jet Emission Linesmentioning
confidence: 99%